Investigation on structural and electrochemical properties of binder free nanostructured nickel oxide thin film - Duraisamy, N.; Numan, A.; Ramesh, K.; Choi, K.H.; Ramesh, S.; Ramesh, S. (2015)
Here, we report a simple method to achieve binder free nickel oxide (NiO) thin film using an electrohydrodynamic atomization (EHDA) process. The optimization of process parameters to obtain uniform thin film is discussed in detail. The high surface purity of nanostructured NiO film is oriented in the face centered cubic structure. The surface morphology revealed uniform deposition of anisotropic nanoplatelets morphology. The cyclic voltammetry and electrochemical impedance spectroscopy confirm the pseudocapacitance behavior of NiO film with a specific capacitance of 178 Fig. The cyclic test exhibits a good cyclic retention of 94% for 1200 cycles. (C) 2015 Elsevier B.V. All rights reserved.